ABOUT DIALOGUE, MONOLOGUE, AND SILENCE IN EDUCATION - ALEVTINA S. Robotova (Высшее образование в России)
The article deals with dialogue, monologue and silence as pedagogical phenomena. The author believes that the focus of modern teachers (scientists, lecturers, school teachers) on dialogue and dialogue technics is often accompanied by a decrease of interest to monologue. However, monologue has its indisputable advantages. Dialogue andmonologue should interact in teaching of Humanities. Silence as a component of speech activity is also noteworthy as it has different pedagogical meanings. The author concludes that in higher education it is necessary to use dialogue, monologue and silence all together.